2004
DOI: 10.1016/j.rmed.2003.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance in patients with COPD

Abstract: We conclude that even non-hypoxemic patients with COPD show significant impairments in cognitive performance. These impairments are not associated with deteriorations in health related quality of life. Prospective evaluation of the impact of treatment on cognitive performance in non-hypoxemic patients with COPD would be a logical subsequent study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
91
1
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 29 publications
(41 reference statements)
9
91
1
11
Order By: Relevance
“…Despite this approach, we found no impact of these indicators of disease severity on the risk of cognitive impairment. This differs from some previous work, 41 but is similar to other studies that found no association between disease severity and cognitive impairment. 42 Our results reveal a disconnect between global measures of COPD severity, which were not related to cognitive impairment, and decreased resting oxygenation, which was strongly associated with decreased cognitive function.…”
Section: Discussionsupporting
confidence: 81%
“…Despite this approach, we found no impact of these indicators of disease severity on the risk of cognitive impairment. This differs from some previous work, 41 but is similar to other studies that found no association between disease severity and cognitive impairment. 42 Our results reveal a disconnect between global measures of COPD severity, which were not related to cognitive impairment, and decreased resting oxygenation, which was strongly associated with decreased cognitive function.…”
Section: Discussionsupporting
confidence: 81%
“…3) Individual characteristics such as age, cultural factors, work status and cognitive capacity [50][51][52][53][54].…”
Section: Questionnaires (Subjective or Self-reported Methods)mentioning
confidence: 99%
“…The clinical implications of an alteration in the autonomic nervous system and cerebrovascular dynamics are clear when considering the recently reported high sensitivity of the solitary tract nucleus to changes in blood flow [38]. Additionally, the alteration in cerebrovascular dynamics may affect cognitive performance [5,6,39]. This, together with blood gas abnormalities occurring in the natural history of COPD, may be an important factor conditioning cognitive impairment seen in these patients [39].…”
Section: Autonomic Disturbances In Copd Patientsmentioning
confidence: 99%
“…In turn, alteration in cerebral blood flow may be an important determinant of the cognitive impairment reported in these patients [5,6], and may also contribute to the worsening of the autonomic and respiratory abnormalities by impairing the perfusion of brainstem regulatory centres. However, smoking is a common habit of COPD patients and, although only few studies (and none in COPD patients) have reported on the chronic effect of smoking on the cerebrovascular dynamics [7][8][9], smoking seems capable of inducing long-term cerebrovascular changes [9].…”
mentioning
confidence: 99%